👤
Mihaaa0411
a fost răspuns

10×{x-10×[362+10×(24+24:4)]}=100

Răspuns :

10*{x-10*[362+10*(24+6)]}=100
10*[x-10*(362+10*30)]=100
10*[x-10*(362+300)]=100
10*(x-10*662)=100
10*(x-6620)=100
10x-10*6620=100
10x-66200=100
10x=100+66200
10x=66300
x=66300/10
x=6630
10 × { x - 10 × [ 362 + 10 × ( 24 + 24 : 4)]} = 100
x - 10 × [ 362 + 10 × ( 24 + 24 : 4)] = 100 : 10 
x - 10 × [ 362 + 10 × ( 24 + 6 ) ] = 10 
x - 10 × ( 362 + 10 × 30 ) = 10 
x - 10 × ( 362 + 300 ) = 10 
x - 10 × 662 = 10 
x - 6 620 = 10 
x = 10 + 6 620 
x = 6 630